2021
DOI: 10.1097/ypg.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hsa-let-7d-5p, hsa-let-7g-5p and hsa-miR-15b-5p plasma levels in patients with Alzheimer’s disease

Abstract: Background Alzheimer's disease (AD) is a progressive neurodegenerative disorder MicroRNAs (miRNAs) may be promising diagnostic biomarkers for AD. Previous evidence shows that miR-15b-5p, hsa-let7g-5p and hsa-let7d-5p might confer potential blood biomarkers for timely diagnosis of AD. Therefore, in this replication study, we aimed to investigate the serum transcript level of these miRNAs to assess for their potential as diagnostic or prognostic biomarker in AD patients. Methods Blood samples were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Subsequent investigations have shown that upregulation of miR-590-5p and miR-142-5p, along with downregulation of miR-194-5p, is distinctive of AD subjects compared to healthy volunteers [ 212 ]. Moreover, enhanced plasma concentrations of hsa-let7d-5p and hsa-let7g-5p were detected in a study comprising 50 AD and 50 age- and gender-matched controls [ 213 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent investigations have shown that upregulation of miR-590-5p and miR-142-5p, along with downregulation of miR-194-5p, is distinctive of AD subjects compared to healthy volunteers [ 212 ]. Moreover, enhanced plasma concentrations of hsa-let7d-5p and hsa-let7g-5p were detected in a study comprising 50 AD and 50 age- and gender-matched controls [ 213 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 relates the main findings on circulatory ncRNA dysregulation in AD [ 17 , 210 , 211 , 212 , 213 , 218 , 220 , 222 , 223 , 224 , 225 , 226 , 227 , 231 , 232 , 233 , 234 , 235 , 237 , 238 , 242 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 ].…”
Section: Resultsunclassified
“…Although in vitro studies indicated possible role of miR-15b-5p in the pathogenesis of Alzheimer’s disease ( 36 ), serum levels of miR-15b-5p were not significantly different between patients with Alzheimer’s disease and healthy subjects ( 72 ).…”
Section: Role Of Mir-15b-5p In Non-malignant Conditionsmentioning
confidence: 99%
“…Multiple reports have examined the regulation of let-7 members in neurodegenerative disease such as AD. Independent replicate studies discovered that expression of both let7g-5p and let7d-5p is significantly increased in blood samples from multiple AD cohorts [ 28 ]. Additionally, a study by Derkow et al, investigated whether brain-localized neurotoxic let-7 transcripts are released into the cerebrospinal fluid (CSF) and could serve as clinical biomarkers [ 23 ].…”
Section: Mirnas In Dementia-related Diseasesmentioning
confidence: 99%